2012
DOI: 10.1096/fj.12-205211
|View full text |Cite
|
Sign up to set email alerts
|

Epididymal protein Rnase10 is required for post‐testicular sperm maturation and male fertility

Abstract: Eutherian spermatozoa are dependent on the environment of the proximal epididymis to complete their maturation; however, no specific epididymal factors that mediate this process have so far been identified. Here, we show that targeted disruption of the novel gene Rnase10 encoding a secreted proximal epididymal protein in the mouse results in a binding defect in spermatozoa and their inability to pass through the uterotubal junction in the female. The failure to gain the site of fertilization in the knockout sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 58 publications
(84 reference statements)
1
43
0
Order By: Relevance
“…Moreover, mouse Spag11a exhibited a region-specific expression pattern and was mainly present in the caput region. This is similar to several genes that are important for sperm maturation such as Rnase10 [34,35], Crisp4 [36,37], and Crisp1 [17], which are exclusively expressed in the initial segment, caput and corpus/cauda, respectively. This region-specific expression is important to create specific environments for sperm maturation.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, mouse Spag11a exhibited a region-specific expression pattern and was mainly present in the caput region. This is similar to several genes that are important for sperm maturation such as Rnase10 [34,35], Crisp4 [36,37], and Crisp1 [17], which are exclusively expressed in the initial segment, caput and corpus/cauda, respectively. This region-specific expression is important to create specific environments for sperm maturation.…”
Section: Discussionmentioning
confidence: 52%
“…Among all these KO genes in male mice, Adam3 is strongly reduced or incorrectly located on the mature epididymal sperm surface. The loss of ADAM3 from the mature sperm surface was also observed after Rnase10 gene KO, a protein secreted only in the initial segment of the epididymis and without any sperm membrane affinities (Krutskikh et al 2012). Such results show that the stability, integrity, and location of ADAM3 at the sperm surface are linked to the presence and/or activities of several other proteins.…”
Section: Epididymal Surroundings and Sperm Proteins Involved In Egg-bmentioning
confidence: 62%
“…Paradoxically the sperm from the mutants are extremely poor at binding firmly to the ZP of eggs, whereas wild-type sperm bind effectively (Figure 4E). Recent studies in the mouse have shown that sperm that have undergone the AR can penetrate an egg, although this was not an efficient process [25], [26] and mouse sperm from several KOs cannot strongly bind to the ZP and yet are still able to fertilize [27], [28].…”
Section: Resultsmentioning
confidence: 99%